Potential for pharmacokinetic interactions between Schisandra sphenanthera and bosutinib, but not imatinib: in vitro metabolism study combined with a physiologically‐based pharmacokinetic modelling approach - Adiwidjaja, Jeffry; Boddy, Alan V.; McLachlan, Andrew J. (British journal of clinical pharmacology, 2020)
Aims This study aimed to investigate the potential interaction between Schisandra sphenanthera, imatinib and bosutinib combining in vitro and in silico methods. Methods In vitro metabolism of imatinib and bosutinib using recombinant enzymes and human liver microsomes were investigated in the presence and absence of Schisandra lignans. Physiologically‐based pharmacokinetic (PBPK) models for the lignans accounting for reversible and mechanism‐based inhibitions and induction of CYP3A enzymes were built in the Simcyp Simulator (version 17) and evaluated for their capability to predict interactions with midazolam and tacrolimus. Their potential effect on systemic exposures of imatinib and bosutinib were predicted using PBPK in silico simulations. Results Schisantherin A and schisandrol B, but not schisandrin A, potently inhibited CYP3A4‐mediated metabolism of imatinib and bosutinib. All three compounds showed a strong reversible inhibition on CYP2C8 enzyme with ki of less than 0.5 μmol L−1. The verified PBPK models were able to describe the increase in systemic exposure of midazolam and tacrolimus due to co‐administration of S. sphenanthera, consistent with the reported changes in the corresponding clinical interaction study (AUC ratio of 2.0 vs 2.1 and 2.4 vs 2.1, respectively). The PBPK simulation predicted that at recommended dosing regimens of S. sphenanthera, co‐administration would result in an increase in bosutinib exposure (AUC ratio 3.0) but not in imatinib exposure. Conclusion PBPK models for Schisandra lignans were successfully developed. Interaction between imatinib and Schisandra lignans was unlikely to be of clinical importance. Conversely, S. sphenanthera at a clinically‐relevant dose results in a predicted three‐fold increase in bosutinib systemic exposure.